Carrier deck launching of adapted land-based airplanes. (August 2020) - Hernando, JL; Martínez-Val, R
VTOL Harrier aircraft has been the basic combat airplane for many Navies, but it will soon be retired from service. Three main alternatives appear: to incorporate another, already existing or under development airplane; to design a completely new aircraft; or to modify an existing land-based airplane to achieve carrier suitability. The present paper is part of a study to assess the feasibility of the third option. In former papers, the authors have addressed, firstly, the compatibility criteria of land-based airplanes with aircraft carriers and, secondly, the details of the approach guidance and the recovery manoeuvre, which showed the need of major modifications in wing structure and landing gear. The research proposed here studies the airplane performance during the take-off manoeuvre from mid-size carriers, formed by a flat deck take-off run followed by a ski-jump and the subsequent flyaway.